ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Liwe, Alther Gabriel; Manossoh, Hendrik; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Audit delay is the length of time from a company’s fiscal year end to the date of the auditor’s report. This research aims to determine the effect of firm size, profitability, and solvability on audit delay in property and real estate company which are listed on the Indonesia Stock Exchange (IDX) period 2012-2016. The samples consist of 38 property and real estates company. The data analysis technique used was multiple linear regression analysis. The results showed that partial firm size does not have any significant effect on audit delay, profitability have significant effect on audit delay, and solvability does not have any significant effect on audit delay, while simultaneously firm size, profitability, and solvability have significant effect on audit delay.Keywords: Audit Delay, Firm Size, Profitability, Solvability